Natural Human Freedoms as the Basis of Legal Regulation - Yu. G. Izotov (Теоретическая и прикладная юриспруденция)
The article provides a new approach to understanding natural human rights. The author reviews the existing concepts of natural law: ancient philosophers, religious ﬁgures of the Middle Ages and the New Age, philosophers of the Enlightenment, I. Kant, the views of modern lawyers, reﬂected in fundamental international documents and national constitutions. It is concluded that the existing concepts are based on assumptions, many of their provisions are outdated and often contradict each other, and the content of the natural human rights themselves is not disclosed. The author is critical of the opinion that natural law is morality or divine law. Instead, it is proposed to build a concept based on the biological characteristics of the human body. To substantiate the new approach, the author applies the method of R. Descartes — denial until the very denial becomes absurd. Thanks to this method, an objective basis was found — «a person exists while he lives», from which further reasoning is conducted. The article provides a logically justiﬁed and integral system of natural human rights, which the author calls “human natural freedoms”. These include natural freedoms: life, consumption, labor, worldview, knowledge and selfdefense. The author proves that they are inalienable, absolute, independent in use and permanent. The article also shows how the objectively existing system of natural human freedoms interacts with positive law. The author notes that the role of such a “bundle” is played by the principles of regulation, which include: universality, equality and fairness. In conclusion, a conclusion is made about the theoretical and practical signiﬁcance of the presented concept.